Sex‐specific behavioral, neurobiological, and cardiovascular responses to chronic social stress in mice. Issue 11 (4th September 2022) - Helman, Tessa J.; Headrick, John P.; Vider, Jelena; Peart, Jason N.; Stapelberg, Nicolas J. C.
Abstract: Psychosocial stress promotes and links mood and cardiovascular disorders in a sex‐specific manner. However, findings in animal models are equivocal, in some cases opposing human dimorphisms. We examined central nervous system (CNS), behavioral, endocrine, cardiac, and hepatic outcomes in male or female C57Bl/6 mice subjected to chronic social stress (56 days of social isolation, with intermittent social confrontation encounters twice daily throughout the final 20 days). Females exhibited distinct physiological and behavioral changes, including relative weight loss, and increases in coronary resistance, hepatic inflammation, and thigmotaxic behavior in the open field. Males evidence reductions in coronary resistance and cardiac ischemic tolerance, with increased circulating and hippocampal monoamine levels and emerging anhedonia. Shared CNS gene responses include reduced hippocampal Maoa and increased Htr1b expression, while unique responses include repression of hypothalamic Ntrk1 and upregulation of cortical Nrf2 and Htr1b in females; and repression of hippocampal Drd1 and hypothalamic Gabra1 and Oprm in males. Declining cardiac stress resistance in males was associated with repression of cardiac leptin levels and metabolic, mitochondrial biogenesis, and anti‐inflammatory gene expression. These integrated data reveal distinct biological responses to social stress in males and females, and collectively evidence greater biological disruption or allostatic load in females (consistent with propensities to stress‐related mood and cardiovascular disorders in humans). Distinct stress biology, and molecular to organ responses, emphasize the importance of sex‐specific mechanisms and potential approaches to stress‐dependent disease. Abstract : Responses to chronic social stress are highly sex‐dependent, although central monoamine signalling is modified in both. Female mice exhibit greater biological disruption including weight loss, inflammation, hepatic and coronary dysfunction and anxiogenesis; males exhibit reduced cardiac stress‐resistance and protective gene expression, and anhedonia (with increased monoamine vs. decreased adipokine levels).